Pengaruh kepemimpinan transformasional dan budaya organisasi terhadap knowledge sharing dan kepuasan kerja - Weny Suci Prasetyaningtyas; Kusdi Raharjo; Tri Wulida Afrianty (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This study aims to investigate the effects of transformational leadership and organizational culture on knowledge sharing and employees’ job satisfaction. This study is an explanatory research with a quantitative approach. The sample of this paper is the employees of PT. AI North Pulau Laut Coal Terminal that are selected based on the proportional random sampling method, resulting in 115 sample number. The primary data is generated by distributing the questionnaires directly to the employees. Data is then statistically analyzed by using Structural Equation Modeling (SEM) and run with Smart PLS 3.0 software. The results empirically support three of the four hypotheses proposed. More specifically, transformational leadership significantly affects knowledge sharing and job satisfaction. Meanwhile, organizational culture has a significantly positive impact on knowledge sharing, but not on job satisfaction. Overall, this study support prior studies and contributes to the literature by highlighting the issue in a research setting that experiences external pressure from declining product prices.